Incidencia de accidentes causados por condiciones inseguras en trabajadores de la construcción de viviendas en la ciudad de Salcedo año 2014. Sistema de control y prevención de accidentes en la construcción de viviendas. - Velasteguí Molina, Santiago Rubén (2015)
This researching study purpose was to analyze the exposure of the building workers to physical, mechanical and chemical factors which may be the accidents reason. And seeks to determine the accidents incidence caused by unsafe conditions on building workers in Salcedo city and develop a control system and accidents prevention. Unsafe building worker conditions are the reasons that increase the accidents. Noise, vibration, inadequate electrical management, disorder at the workplace, handle of tools short sharp, dust exposure, chemicals handling, can cause serious damage to the health and physical integrity of workers. Everybody has the option to develop their activities in a proper and conducive environment that ensures their health, integral, hygiene and welfare. Through the use practical methods and tools like interviews, surveys, and triplestep matrix, we obtained results that are agree and confirm the presented hypothesis because workers say that the noise, machine vibration, and tool short stabbing are moderate risks, while the disorder at workplace, dust exposure, chemicals handling become a major risk and the improper electric operation, ladders and scaffolds tatty are an intolerable risk, concluding it's necessary to incorporate measurements to minimize these risks, finally we developed a control system and accidents in the building of houses.